Pengaruh Program Kredit Usaha Rakyat (KUR) terhadap Efisiensi dan Pendapatan Kelompok Usaha Bersama (KUBE) Penggemukan Sapi di Lampung Tengah - Heru Wahyudi; Mahmud Mahmud (Studi Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This research aims to determine the effect of the People’s Business Loans (KUR) on income and the level of efficiency in the use of production factors by members of the Delapan Jaya joint business group (KUBE) in Central Lampung in 2018-2019 which is divided into six business cycle periods. Research methodology: The analytical method used in this research is quantitative descriptive with primary data. Results: The results of this research indicate that KUR funds have a positive effect on income with an average value of 13.02% or with an average KUBE profit of IDR 123,030,367 from the total KUR fund allocation of IDR 945,000,000. Meanwhile, the smallest production factor efficiency index was 1.84 and the largest efficiency index was 2.02. So, that the average efficient index is 1.96 which means that the use of production factors is not efficient. So, that the use of production factors for feed ingredients and medicines can still be added. Limitations: The limitation of this study is to use quantitative descriptive without looking at the effect of independent variables on income (without regression analysis). Contribution: The results obtained from this study are expected to be one of the references in making the use of larger cattle breeds and by increasing the use of feed costs because feed costs can still be increased as long as the efficiency index is still l > 1.